Comparison of different thermal treatments on the physicochemical properties of Apios fortunei used for yellow wine fermentation. (June 2021) - Bian, Shichao; Xu, Enbo; Fu, Xi; Jin, Zhengyu; Jiao, Aiquan
Abstract: A novel material ( Apios fortunei ), which has a high starch content and potential healthcare functions, was used for yellow wine fermentation. To determine how the tuber's composition would be modified by thermal treatments and how those modifications would affect fermentation, the changes in the physicochemical properties of the A. fortunei tuber after steam cooking, traditional extrusion (extrusion without enzyme) and enzymatic extrusion (introduce the amylase into the extrusion) were investigated. The results showed a low degree of gelatinization (70.56%) in the steam-cooked sample, and the fermentation broth of the traditionally extruded sample was dense. However, the enzymatically extruded sample was almost completely gelatinized (99.09%) with an amorphous starch structure measured via X-ray diffraction and Fourier-transform infrared spectroscopy. The high water solubility index (61.66%), low water absorption index (1.68 g/g) and viscosity (<60 cP), indicated that the broth of enzymatically extruded sample had a fine fluidity. The results of the final wines indicated that enzymatic extrusion significantly increased the fermentation efficiency, from 62.22% (steam cooking) and 63.87% (traditional extrusion) to 73.47%. Meanwhile, enzymatic extrusion improved the quality characteristics of the final wines, including total amino acid (4559.20 mg/L), soluble solid content (7.35 g/100 g) and total acid (10.66 g/L). Highlights: Apios fortunei tubers were proved to have the potential to produce yellow wine. Enzymatically extruded Apios has low viscosity, crystallinity and a porous surface. Enzymatic extrusion increased fermentation efficiency of Apios wine. The quality characteristics of Apios wine were improved by enzymatic extrusion.